From ice age to modern: a record of landscape change in an Andean cloud forest - Valencia, B. G.; Urrego, D. H.; Silman, M. R.; Bush, M. B. (Journal of Biogeography, 2010)
Aim
id: 869; 639ND Times Cited:5 Cited References Count:63Y